Evaluasi Nilai Kekerasan Resin Komposit Bulkfill dengan Variasi Waktu Penyinaran Sinar LED - Atia Nurul Sidiqa; Badi Soerachman; Mutiara Yulina Putri (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2018)
Bulkfill composite resin can be applied in “bulk” up to 4mm and it can be cures with LED curing lights in 10 seconds. Time exposure affects the hardness of the composite resin material. This experiment aims to determine differences in exposure time with LED on the hardness of bulkfill composite resin. This experiment is a true experiment. The samples are bulkfill composite resin with diameter of 6 mm and thickness of 4 mm. There were 3 groups of samples (n=5) and cured with LED with intensity 1000mW/cm2. Group 1 was exposed for 10 seconds, group 2 for 20 seconds, and group 3 for 40 seconds. The samples were soaked in distilled water 37oC for 24 hours in waterbath. Microvickers hardness with the load of 100 grams in 15 seconds applied to the samples on the lower and the upper surface. The result found that the ratio of hardness both 10 seconds and 20 seconds, and 20 seconds and 40 seconds are no significant. The ratio hardness of 10 seconds and 40 seconds had significant difference. Based on the research irradiation time effect resin bulkfill composite hardness. It means that the more monomer polymerized the more higher hardness could be achived. The longer exposure time can make increases hardness level.